An Analysis Of English Pronunciation In The Sixth Grade - Nila Sari Dewi; Juni Hartiwi; Sulastri Sulastri; Sri Sutiwi (Departement of Mathematics Education, 2024)
Learning English is very important for student especially in the elementary school. The first important thing is to train their tongue in order they are accustomed to hear English words. The intelligence of boy students is higher than girl students. It is happened because of some factors. First, a girl is braver than a boy. Second, a girl likes to interact than a boy. The third, a girl is clever to open their mouth so appear the movement in their lips and their tongue. Thus, from those factors influence the pronunciation of a girl better than boy. The formulation of the problem of this analysis is how the phonetic transcription of pronunciation of students in the sixth grade in terms of manner of articulation in SD Negeri Bumijaya. In doing the analysis the researcher used some theories that have relation with the topic, they are language, phonology which consists of phonetics, phonemics, and manner of articulation. Psycholinguistics and sociolinguistics are part of concept used to sustain the analysis. In conclusion, gender influences pronunciation. Here there are differences pronunciation between boys and girls. Having done the analysis, the researcher concludes that 30% boy students are able in pronouncing the words and 46% girl students are able in pronouncing the words.